RETICENCE DE LA POPULATION A LA PROCREATION DES PERSONNES VIVANT AVEC LE VIH/SIDA A KISANGANI EN REPUBLIQUE DEMOCRATIQUE DU CONGO. - LIFOLI BALEA, Jean-Pierre; AWESSE, Christian MASSABA (IJRDO - Journal of Social Science and Humanities Research, 2018)
The population of Kisangani in Democratic Republic of Congo comes out of a transition prolonged from 1990 to 1997, of a war that ended in 2003, of a post-war difficult socioeconomic situation. The struggle against the VIH/SIDA of which the sensitization, the tracking voluntary of mass began in 2005 with the advent of the struggle multisectory. Unfortunately this struggle multisectory only made five years, without an assessment of the impact on the knowledge, attitudes and behaviors of the concerned persons facing the VIH/SIDA. on the other hand, the fear of the VIH/SID and his consequences brings to the fear of the tracking and a resistance to all what milked in the VIH/SIDA. From where this reticence of the population of Kisangani to the procreation of people living with the VIH/SIDA.